The East European Craton (Baltica) before and during the assembly of Rodinia - Bogdanova S.V.; Bingen B.; Gorbatschev R.; Kheraskova T.N.; Kozlov V.I.; Puchkov V.N.; Volozh Yu.A. (My University, 2008)
Prior to participating in Rodinia, the East European Craton (Baltica) had undergone a complex process of development. Many of the structures, which were important during the amalgamation of Rodinia, were formed between ca. 1.7 and 1.4Ga. From ca. 1.6Ga onwards, the evolution of the western and eastern parts of this Craton followed very different path. While accretion of juvenile continental crust, and eventually, continental collision took place in the west, rifting and extension consistently dominated in the east. Between 1.14 and 0.90Ga, the Sveconorwegian orogeny marked the incorporation of the East European Craton (Baltica) into Rodinia. This process involved four distinct phases related to Baltica’smovements.During the 1.14–1.10GaArendal phase therewas accretion and early collision, during the 1.05–0.98Ga Agder phase continent–continent collision took place, while the 0.98–0.96Ga Falkenberg phase and the 0.96–0.90Ga Dalane phase involved ﬁnal convergence and post-collisional relaxation, respectively. The differences of tectonic regime in the East European Craton during the late Mesoproterozoic were determined by the movement and rotation of this megaterrane concomitantly with the Rodinia assembly. This led to collisional tectonics in the present west while break-up and the formation of passive margins occurred in the east.
Keywords: Rodinia; East European Craton; Baltica; Mesoproterozoic; Sveconorwegian orogeny; Rifting; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская